Perbedaan Hasil Belajar Matematika Menggunakan Model Pembelajaran Matematika Realistik (PMR) dan Model Pembelajaran Problem Based Learning (PBL) pada Siswa Kelas V Sekolah Dasar - Imam Pujo Prasetyo Adi; Henny Dewi Koeswanti (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract This study aims to determine the influence of the use of Realistic Mathematics Education models and modelsProblem Based Learning (PBL) on Mathematics learning outcomes in fifth grade students. This research uses the methodas if experimentalwith experimental designPost-test Only Control Group Design. Data collection using test techniques. The results show that there is an effect of using the Indonesian Realistic Mathematics Education (PMRI) model and modelsProblem Based Learning (PBL) on Mathematics learning outcomes in class V students with an average scorePost-Test The PMR experiment was 84.07 with a standard deviation of 8.375 and a maximum value of 97 and a minimum of 70. As for the average value of the Post-Test Experiment PBL was 75.67 with a standard deviation of 9.389 and a maximum value of 93 and a minimum value of 53. Then the results were obtained independent sample t-test test which produces a sig value. (2-tailed) of 0.001 <0.05, which means there is a significant difference. Keywords: Realistic Mathematics Learning Model (PMR), Learning Model, Problem Based Learning (PBL), Mathematics Learning Outcomes Abstrak Penelitian ini bertujuan untuk mengetahui adanya pengaruh penggunaan model Pendidikan Matematika Realistik dan model Problem Based Learning (PBL) terhadap hasil belajar Matematika pada peserta didik kelas V. Penelitian ini menggunakan metode quasi experimental dengan desain eksperimen Post-test Only Control Group Design. Pengumpulan data menggunakan teknik test. Hasil menunjukan terdapat pengaruh penggunaan model Pendidikan Matematika Realistik Indonesia (PMRI) dan model Problem Based Learning (PBL) terhadap hasil belajar Matematika pada peserta didik kelas V dengan nilai rata-rata Post-Test Eksperimen PMR adalah 84,07 dengan standar deviasi 8,375 serta nilai maksimum 97 dan minimum 70. Sedangkan untuk nilai rata-rata Post-Test Eksperimen PBL adalah 75,67 dengan standar deviasi 9,389 serta nilai maksimum 93 dan nilai minimum 53. Kemudian didapatkan pula hasil uji independent sample t-test yang menghasilkan nilai sig. (2-tailed) sebesar 0,001 < 0,05 yang artinya terdapat perbedaan yang signifikan. Kata Kunci: Model Pembelajaran Matematika Realistik (PMR), Model Pembelajaran, Problem Based Learning (PBL), Hasil Belajar Matematika